Leading the Way: Multi‐Drug Resistance Protein (MDR1) and Clinical Pharmacology—Commentary on Kim et al - Giacomini, Kathleen M. (Clinical pharmacology and therapeutics, 2025)
Over the last three decades, transporters have become increasingly recognized for their important roles in clinical pharmacology. As gatekeepers of drug absorption, disposition and targeting, transporters in the intestine, liver, kidney and blood brain barrier have been the subject of many clinical pharmacology studies. A seminal work published in 2001 was among the first studies to shift the focus of pharmacogenomic research from drug metabolizing enzymes to drug transporters, demonstrating that pharmacogenomic factors in genes in addition to drug metabolizing enzymes, and in particular, in transporter genes, could play an important role in interindividual variation in pharmacokinetics of drugs.